A Modernist Approach to T.S Eliot’s The Love Song of J. Alfred Prufrock - Güven, Samet (Journal of History Culture and Art Research, 2015)
A Modernist Approach to T.S Eliot’s “The Love Song of J. Alfred Prufrock" Abstract T.S. Eliot’s The Love Song of J. Alfred Prufrock carries the characteristics of modernist poetry such as objective correlative, fragmentation, free verse and irregular rhyming. It suggests a direct break with English romantic poets such as Coleridge and Wordsworth (Levis 75). Sara Thorne states that unlike the Romantic poets, Eliot attempts to convey the essence of life; and the content represents actual contemporary life rather than an escape from the grinding nature of reality (281). ’The Love Song of J. Alfred Prufrock’ exemplifies Thorne’s definition of Eliot’s poetic art clearly. The poem is about a middle-aged man who cannot make a progress in life and dare to approach women due to his timidity. Hence, the title of the poem is ironic since Prufrock never talks about his feelings of love throughout the poem. His indecisiveness is also caused by self-isolation from the society as a modern man. He finds himself in a society which is not different from a hell for him, so Eliot portrays the complexities of the modern world vividly through the inconsistent psychology of Prufrock. Elisabeth Schneider clarifies that ’The Love Song’ is more than a retreat from love, however; it is the portrait of a man in Hell, though until his truth is clearly realized, the hell appears to be merely the trivial one of the self-conscious individual in a sterile society (1104). Apart from the content, in the form Eliot uses objective correlative to relate feelings through the use of objects. The poem focuses on the dilemma caused by modern urban civilization and therefore, the purpose of this paper is to show how T.S. Eliot’s The Love Song of J. Alfred Prufrock reflects modernism in terms of its content and structure respectively.